Analisis Faktor-faktor Yang Mempengaruhi Kejadian Bayi Berat Lahir Rendah di PMB Andina Palembang - Suci Sulistyorini (Masker Medika, 2022)
One of the indicators of a country's success in improving public health is by decreasing the infant mortality rate (IMR). The most common cause of neonatal death is low birth weight (LBW). 2017 shows AKN of 15 per 1,000 live births, IMR of 24 per 1,000 live births, and AKABA 32 per 1,000 live births. The incidence of LBW is still quite high in the city of Palembang, Based on data from the Independent Practice Report of Midwife Andina Primitasari Palembang, it was found that the incidence of LBW in 2018 was 10 events, in 2019 11 events and in 2020 the period January 1 to May 30 totaled 11 events. This study aims to analyze the factors that influence the incidence of low birth weight babies in PMB Andina Primitasari Palembang. The design of this study used an analytical survey method with a case control research design. The population in this study were all newborns who were recorded as being born in PMB "X" Palembang for the period January 1 to May 30, 2020. The research sample was case: control comparison 1: 1. The subject of the case study was 32 LBW infants and the control was low birth weight infants. Normal number is 32 babies. Sampling technique is simple random sampling. The analysis used univariate and bivariate with Chi-Square. The research was conducted at PMB Andina Primitasari Palembang in June 2020. Based on univariate analysis, the incidence of LBW was 32 (50%) and not LBW was 32 (50%). Birth spacing is not at risk 73.4% and at risk 26.6%, gestational age at term 87.5% preterm 12.5%, not gammeli 89.1%, gammeli 10.9%, not anemic 76.6% and anemia 23, 4%. Based on bivariate data, it was found that there was a relationship between birth spacing (p value = 0.048), gestational age (p value = 0.002), gammeli (p value = 0.005), and anemia (p value = 0.039) to the incidence of low birth weight babies in PMB. Andina Palembang. It is recommended to health workers that preventive efforts are needed with counseling and counseling for pregnant women to pay attention to nutritional intake and carry out antenatal care regularly and comply with the counseling given by health workers so that the mother's pregnancy is normal without complications and the baby is in a healthy condition.